THE IMPACT OF MOBILE PHONES ON ELEMENTARY STUDENTS - Malik Ibrahim (Edelweiss : Journal Of Innovation In Educational Research, 2026)
The development of science and technology at this time is increasingly rapid and creates technological products that provide many benefits and make it easier for humans to know science, education and entertainment. All of that can be obtained by using access through the internet, one of which is most interested in online games is children. Because these online games are synonymous with playing. This online game is a new style that has many enthusiasts, both young and old, and currently we find many in crowded areas of stalls that use the internet network as well as in the village or in the city. And they facilitate the internet to attract customers. In the past, children only knew traditional games, usually played by other friends directly, such as playing marbles and hide and seek. While the game itself is their own thought. Along with the flow of globalization with the demands of the need for rapid information exchange, the role of communication technology has become very important. So that users are uncontrollable in terms of using a technology